RNA G-Quadruplex within the 5'-UTR of FEN1 Regulates mRNA Stability under Oxidative Stress - Ying Ma; Yang Yang; Jingyu Xin; Lingfeng He; Zhigang Hu; Tao Gao; Feiyan Pan; Zhigang Guo (MDPI AG, 2023)
Reactive oxygen species (ROS) are a group of highly oxidative molecules that induce DNA damage, affecting DNA damage response (DDR) and gene expression. It is now recognized that DNA base excision repair (BER) is one of the important pathways responsible for sensing oxidative stress to eliminate DNA damage, in which FEN1 plays an important role in this process. However, the regulation of FEN1 under oxidative stress is still unclear. Here, we identified a novel RNA G-quadruplex (rG4) sequence in the 5'untranslated region (5'UTR) of FEN1 mRNA. Under oxidative stress, the G bases in the G4-forming sequence can be oxidized by ROS, resulting in structural disruption of the G-quadruplex. ROS or TMPyP4, a G4-structural ligand, disrupted the formation of G4 structure and affected the expression of FEN1. Furthermore, pull-down experiments identified a novel FEN1 rG4-binding protein, heterogeneous nuclear ribonucleoprotein A1 (hnRNPA1), and cellular studies have shown that hnRNPA1 plays an important role in regulating FEN1 expression. This work demonstrates that rG4 acts as a ROS sensor in the 5'UTR of FEN1 mRNA. Taken together, these results suggest a novel role for rG4 in translational control under oxidative stress.